From Bahong Flower Farms to the Dangwa Flower Market: Tracing the flow of cut-flowers, agents, and local knowledge - Mercurio, Dale V.; Ng, Garrick S.; Pagdanganan, Jonahlyn Rose S.; Guazon, Hector (anthropozine: The Official Publication of the University of the Philippines H. Otley Beyer Museum of Anthropology, 2025)
This study shows how local knowledge corresponds to (un)certainties brought forth by socioeconomic forces and crisis moments in the production of flowers in Bahong and beyond, the ways local knowledge may be reconfigured due to material (im)mobility, and the various third-party inclusions and systems that have affected the process of distribution.